ANALYSIS OF THE INFLUENCE OF TEMPERATURE, EQUIVALENCE RATIO (ER) AND GASIFYING AGENT AGAINST COLD GAS EFFICIENCY (CGE) AND TAR: SISTEMATIC LITERATURE REVIEW - RAHMAH, DEWI ANISA; NURHILAL, OTONG (Jurnal Material dan Energi Indonesia, 2025)
The global energy transition to renewable sources places biomass and gasification technologies as crucial solutions for producing syngas. The Systematic Literature Review (SLR) analyzed the influence of operational parameters, namely Temperature, Equivalent Ratio (ER) and Gasification Agent on Cold Gas Efficiency (CGE) and Tar in biomass gasification. Based on the PRISMA methodology and the analysis of 30 selected articles, it was found that temperature has a non-linear and critical relationship. CGE reaches a peak of 75% in the range of 750°C to 800°C, while tar reduction occurs above 800°C through a thermal cracking mechanism. The optimal ER value was identified at 0.37 which resulted in a maximum concentration of flammable gases of H2 and CO with minimal tar. In addition, gasification agents such as flue gas show better quality syngas than air. By design, the downdraft type reactor proved to be superior with a much lower tar concentration of 0.05-0.45 g/Nm3 compared to the updraft type of 10.9 g/Nm3. The SLR results underscore the importance of multivariable parameter optimization for efficient and reliable gasification performance.